Genomic and in-situ Transcriptomic Characterization of the Candidate Phylum NPL-UPL2 From Highly Alkaline Highly Reducing Serpentinized Groundwater - Suzuki, Shino; Nealson, Kenneth H.; Ishii, Shun’ichi (Frontiers in Microbiology, 2018)
Serpentinization is a process whereby water interacts with reduced mantle rock called peridotite to produce a new suite of minerals (e.g. serpentine), a highly-alkaline fluid, and hydrogen. In previous reports, we identified abundance of microbes of the candidate phylum NPL-UPA2 in a serpentinization site called The Cedars. Here we report the first metagenome assembled genome (MAG) of the candidate phylum as well as the in-situ gene expression. The MAG of the phylum NPL-UPA2, named Unc8, is only about 1 Mbp and its biosynthetic properties suggest it should be capable of independent growth. In keeping with the highly reducing niche of Unc8, its genome encodes none of the known oxidative stress response genes including superoxide dismutases. With regard to energy metabolism, the MAG of Unc8 encodes all enzymes for Wood-Ljungdahl acetogenesis pathway, a ferredoxin:NAD+ oxidoreductase (Rnf) and electron carriers for flavin-based electron bifurcation (Etf, Hdr). Furthermore, the transcriptome of Unc8 in the waters of The Cedars showed enhanced levels of gene expression in the key enzymes of the Wood-Ljungdahl pathway (e.g. Carbon monoxide dehydrogenase /Acetyl-CoA synthase complex (CODH/ACS), Rnf, Acetyl-CoA synthetase (Acd)), which indicated that the Unc8 is an acetogen. However, the MAG of Unc8 encoded no well-known hydrogenase genes, suggesting that the energy metabolism of Unc8 might be focused on CO as the carbon and energy sources for the acetate formation. Given that CO could be supplied via abiotic reaction associated with deep subsurface serpentinization, while available CO2 would be at extremely low concentrations in this high pH environment, CO-associated metabolism could provide advantageous approach. The CODH/ACS in Unc8 is a Bacteria/Archaea hybrid type of six-subunit complex and the electron carriers, Etf and Hdr, showed the highest similarity to those in Archaea, suggesting that archaeal methanogenic energy metabolism was incorporated into the bacterial acetogenesis in NPL-UPA2. Given that serpentinization systems are viewed as potential habitats for early life, and that acetogenesis via the Wood-Ljungdahl pathway is proposed as an energy metabolism of Last Universal Common Ancestor, a phylogenetically-distinct acetogen from an early earth analogue site may provide important insights in primordial lithotrophs and their habitat.